CIAT SOC APP - Sommer, Rolf; Koech, Nicholas; Godiah, David (2015)
There has been quite some debate about the scope for mitigating climate change by soil organic carbon (SOC) sequestration. However, it seems there is a general lack of understanding of quantities and the time-dimension, as well as the possible contribution that SOC sequestration can play. This web application provides a platform where users can visualize the organic carbon content of a soil of their choice, as well as the quantitative impact of soil conserving management practices on sequestration, how such sequestration would unfold over time and what would be the magnitude of SOC sequestration if the anticipated practice (to foster SOC seq.) would be scaled out to countries, sub-continents or the entire world. The basis of the idea is the publication from Sommer and Bossio 2014 (Dynamics and climate change mitigation potential of soil organic carbon sequestration. J. Environm. Management 144, 83-87). This study is part of the CGIAR Research Program on Water, Land and Ecosystems (WLE). The CIAT SOC APP is a soil organic content computation tool that computes SOC concentration and sequestration of a given soil, and outputs the results in graphic and table formats. The tool is open-access to be use by individuals, governments, NGOs, researchers, communities, and others. We are happy to share the source code upon enquiry.